Nanocompósitos de alginato/CdSe e carbon dots fluorescentes para aplicações em sensores - Nascimento, Keyte Nayara da Silva (2021)
The properties and versatility that emerge from nanomaterials, such as quantum dots (QDs) and the carbon dots (C-dots), expand the possibility of their applications. In this work, CdSe QDs, with optimized optical properties, were synthesized via a ligandexchange method and by varying the pH reaction. Among all the samples, the one prepared using N-acetyl cysteine (NAC) as the stabilizing agent at pH 10 presented the higher photoluminescence (PL) emission intensity. CdSe/NAC QDs were later conjugated with alginate (ALG) in order to produce a composite film. Those films were submitted to thermal studies with 14 cycles, each one representing the heating of the material from 20°C to 90°C in order to analyse the PL emission decay of the composite films as a function of temperature. The results showed that after 24 hours the composite film recovers its fluorescent properties. The reversibility in PL emission in relation to temperature variation indicates a potential application of that composite films as a photothermal sensor. In addition, ALG-based C-dots were synthesized via hydrothermal synthesis with the aim of using them for analyte detection systems. The results showed the viability C-dots of ALG for the detection of Ni2+ and Cu2+ ions, being more sensitive for the Cu2+ ion, due to chelation kinetics on the surface of C-dots. Among the detection systems for volatile organic compounds (VOCs) – toluene, hexane, propanol and propanone – propanone showed the best response, with a 72% decay in PL emission, a consequence of its strong electron donor character.